Differential Effect of Cytomegalovirus Infection with Age on the Expression of CD57, CD300a, and CD161 on T-Cell Subpopulations - Hassouneh, Fakhri; Lopez-Sejas, Nelson; Campos, Carmen; Sanchez-Correa, Beatriz; Tarazona, Raquel; Solana, Rafael; Pera, Alejandra (Frontiers in Immunology, 2017)
Immunosenescence is a progressive deterioration of the immune system with ageing. It affects both innate and adaptive immunity limiting the response to pathogens and to vaccines. As chronic cytomegalovirus (CMV) infection is probably one of the major driving forces of immunosenescence, and its persistent infection results in functional and phenotypic changes to the T-cell repertoire, the aim of this study was to analyze the effect of CMV-seropositivity and ageing on the expression of CD300a and CD161 inhibitory receptors, along with the expression of CD57 marker on CD4+, CD8+, CD8+CD56+ (NKT-Like) and CD4−CD8− (DN) T-cell subsets. Our results showed that, regardless of the T-cell subset, CD57−CD161−CD300a+ T-cells expand with age in CMV-seropositive individuals, whereas CD57−CD161+CD300a+ T-cells decrease. Similarly, CD57+CD161−CD300a+ T-cells expand with age in CMV-seropositive individuals in all subsets except in DN cells and CD57−CD161+CD300a− T-cells decrease in all T-cell subsets except in CD4+ T-cells. Besides, in young individuals, CMV latent infection associates with the expansion of CD57+CD161−CD300a+ CD4+, CD57−CD161−CD300a+ CD4+, CD57+CD161−CD300a+ CD8+, CD57−CD161−CD300a+ CD8+, CD57+CD161−CD300a+ NKT-like and CD57+CD161−CD300a+ DN T-cells. Moreover, in young individuals, CD161 expression on T-cells is not affected by CMV infection. Changes of CD161 expression were only associated with age in the context of CMV latent infection. Besides, CD300a+CD57+CD161+ and CD300a−CD57+CD161+ phenotypes were not found in any of the T-cell subsets studied except in the DN subpopulation, indicating that in the majority of T-cells CD161 and CD57 do not co-express. Thus, our results show that CMV latent infection impact on the immune system depends on the age of the individual, highlighting the importance of including CMV serology in any study regarding immunosenescence.